Living alone and deliberate self-harm: A case-control study of characteristics and risk factors - Haw, C; Hawton, K (2011)
Background An increasing proportion of the UK population live alone. Little is known about deliberate self-harm (DSH) patients who live alone. We conducted a study of the characteristics of DSH patients who live alone using data from the Oxford Monitoring System for Attempted Suicide. Method Data on patients presenting to the general hospital in Oxford with an episode of DSH between 1993 and 2006 were analysed by gender and age group (15-24 years, 25-54 years and 55? years) and according to whether or not they lived alone. Results In total, 1,163/7,865 (14.8%) patients lived alone. Having a problem with social isolation was more common in those living alone compared with those living with others, especially in those aged 55? years. In the 25-54 years age group several variables concerning psychiatric problems were more common in those living alone, as was higher suicide intent associated with the current DSH episode and past DSH, and for females, repetition of DSH within 12 months. In patients aged 55? years those living alone were more likely to have problems due to bereavement. Significantly more individuals living alone died from any cause. More also died by suicide, although the difference between the groups was non-significant after adjusting for age. Conclusions These results have implications for psychiatric services assessing DSH patients who live alone, since, depending on the patient's age and living circumstances, different psychiatric and social interventions may be needed. Middle-aged DSH patients who live alone appear to be particularly vulnerable. DSH patients who live alone may not have supportive social networks and may be at increased risk of repetition of DSH and suicide. © Springer-Verlag 2010.